Study on combined heat pump drying with freeze‐drying of Antarctic krill and its effects on the lipids. Issue 6 (28th May 2017) - Sun, Dewei; Cao, Chen; Li, Bo; Chen, Hongjian; Cao, Peirang; Li, Jinwei; Liu, Yuanfa
Abstract: To better preserve quality of Antarctic krill for wide food application, a drying method by the combining both the heat pump drying (HPD) and freeze‐drying (FD) was investigated. The effect on its dehydration efficiency, and effects on lipid extraction rate and lipid qualities and cost of the process were compared. The Antarctic krill was first treated by HPD, followed by the FD method. The lipids extracted from the various dehydrated samples were compared. In addition, the time and energy consumption during the process of dehydration and the physical properties such as color and microstructure of the Antarctic krill samples dehydrated by various drying methods were also compared. The results indicated that Antarctic krill drying by combined dehydration had good color and microstructure, which were both close to the FD sample, and better than the heat pump and hot air drying samples alone. The procedure was performed with an optimal dehydration temperature of HPD at 60 °C and a transition point of 40% moisture content, followed by freezing‐drying up to moisture content of 10%. Lipids extracted from Antarctic krill dried through procedure would have high lipid extraction rate (21.02%), low acid value (10.4 mg KOH/g), high astaxanthin content (200 mg/kg). Importantly it would save about 62 and 50%, respectively, of time and energy consumption in comparison of freezing‐drying method. Therefore, this study was for the first time to show that the combined dehydration of HPD and FD could be viable applicable dehydration method for Antarctic krill treatment. Practical applications: HPD can provide efficient dehydration with a low temperature and energy consumption for high water content materials. The combined dehydration procedure of HPD and FD for Antarctic krill treatment could supply excellent quality of Antarctic krill as foodstuffs and for its further processes such as lipid extraction. This procedure would be more feasible for the food industrial processes.